Legitimacy Through Constructive Engagement: An Institutional Pressure Perspective to Primary Sector MNE Social Sustainability in the Republic of Liberia - Karinen, Matti (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Primary sector Multi-National Enterprises (MNEs) in developing countries are the subject of intense concern regarding their social, environmental and economic sustainability. MNEs investing in emerging economies need to be able to adapt and work in a challenging institutional environment governing the legitimacy of their activities. The study uses Institutional Theory and the concept of Institutional Pressure to analyse the process of Pressure and Response by which the social sustainability legitimacy of an MNE project was constructed on different levels. The purpose of the study is to understand how primary sector MNEs operating in complex developing country contexts respond to a variety of institutional pressures to demonstrate legitimacy in terms of project sustainability? Drawing on the case of a Roundtable on Sustainable Palm Oil (RSPO) certified Oil Palm company in the Republic of Liberia, this study provides insight into the process by which MNEs negotiate a complex multi-layered institutional environment that seeks a balance between the needs and requirements of the company, the host community and those of domestic and international institutional actors. The specific case in this case study revolves around the implementation of a social sustainability principle, FPIC, by the MNE and the institutional pressure brought to bear on the company by a number of actors including host government, host community, local and international NGOs and an international certification body. The central finding of the study can be encapsulated thus: instead of a single universal legitimacy, Primary Sector MNEs hold bundles of potentially contradictory legitimacies. These are held with different institutions in different contexts. They may support one another, or be in conflict, and may be either more, or less, important to the organization from time to time. This is combined with the caveat that these legitimacies are grounded in the legitimacy of the relationship between the MNE and Host community. MNEs can demonstrate this legitimacy to other institutional actors through a documented process of constructive engagement that leads to the existence of a state of Social Licence to Operate – a defined form of social sustainability. It is suggested that an important part of constructive engagement for primary sector MNEs in developing countries is the application of a thorough Free Prior and Informed Consent (FPIC) procedure in before and through-out project work.